Case Report: Membranous Nephropathy Secondary to Cobalamin C Disease - Wang, Qiang; Wang, Qi; Gao, Yanxia; Tang, Chenquan; Gao, Zhaoli; Hu, Zhao (Frontiers in Medicine, 2022)
Background: Mutation of MMACHC causes inherited cobalamin C disease with methylmalonic academia (MMA) and homocysteinemia. Renal complications may also be present in patients with this deficiency. However, membranous nephropathy secondary to cobalamin C disease has not been reported to date. Case presentation: We encountered a 17-year-old female patient with a trans-compound mutation of MMACHC who presented with membranous nephropathy, MMA, homocysteinemia, and hyperuricemia. The mutations of c.80A>G (chr1:45966084) and c.482G>A (chr1:45974520) (predicting p.Gln27Arg and p.Arg161Gln missense changes at the amino acid level) had been inherited from her father and mother, respectively. Hydroxocobalamin, betaine, and L-carnitine were administered. The patient achieved complete remission of the membranous nephropathy and resolution of the MMA, homocysteinemia, and hyperuricemia. Conclusion: Membranous nephropathy secondary to cobalamin C disease is reversible with timely intervention.